Endoscopic Removal of a Single, Painless, Juvenile Polyp in the Small Intestine Causing Anemia. Issue 4 (October 2020) - Krasaelap, Amornluck; Lerner, Diana; Southern, James; Noe, Joshua; Chugh, Ankur
Abstract : ABSTRACT: Juvenile polyps are the most common gastrointestinal polyps in childhood. Typically, they are located in the colon and present with intermittent and painless hematochezia. A few case reports have described juvenile polyps in the small intestine, all presenting as intussusception requiring surgery. We report an isolated juvenile polyp in the small intestine presenting with painless anemia, identified using video capsule endoscopy, and removed via enteroscopy.